2018
DOI: 10.1182/blood-2017-09-807156
|View full text |Cite
|
Sign up to set email alerts
|

Bim regulates the survival and suppressive capability of CD8+ FOXP3+ regulatory T cells during murine GVHD

Abstract: CD8 Foxp3 T cells (Tregs) are a potent regulatory population whose functional and ontological similarities to CD4 Fox3 T cells have not been well delineated. Using an experimental model of graft-versus-host disease (GVHD), we observed that CD8 Tregs were significantly less potent than CD4 Tregs for the suppression of GVHD. To define the mechanistic basis for this observation, we examined the T-cell repertoire and the transcriptional profile of in vivo-derived CD4 and CD8 Tregs that emerged early during this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Although CD8+ iTregs expressed higher levels of suppressive molecules like CD39 + CD73 + , CTLA-4, and granzyme than CD4+ iTregs, there was no difference observed between their in vitro suppressive functions ( 82 ). In contrast to their in vitro suppressive functions, CD8+ iTregs are less potent than CD4+ iTregs in controlling GVHD due to their pro-apoptotic phenotype and thus reduced survival but are more effective in eliminating leukemia cells ( 82 , 225 ). Intriguingly, CD8+ iTreg expression of FoxP3 can be stabilized by JAK2 targeting ( 226 ).…”
Section: Cellular Therapiesmentioning
confidence: 98%
“…Although CD8+ iTregs expressed higher levels of suppressive molecules like CD39 + CD73 + , CTLA-4, and granzyme than CD4+ iTregs, there was no difference observed between their in vitro suppressive functions ( 82 ). In contrast to their in vitro suppressive functions, CD8+ iTregs are less potent than CD4+ iTregs in controlling GVHD due to their pro-apoptotic phenotype and thus reduced survival but are more effective in eliminating leukemia cells ( 82 , 225 ). Intriguingly, CD8+ iTreg expression of FoxP3 can be stabilized by JAK2 targeting ( 226 ).…”
Section: Cellular Therapiesmentioning
confidence: 98%
“…Indeed, suppressive properties of CD8 + FOXP3 + T cells in vitro and in vivo have been documented by multiple studies in mice, human, and nonhuman primates [915, 18]. A transcriptomic analysis showed that the gene expression profile of induced murine (m) CD8 + FOXP3 + Tregs is distinct from conventional CD8 + T cells, but similar to CD4 + Tregs [19]. Common phenotypic features of CD8 + FOXP3 + T cells and CD4 + Tregs include expression of CD25, CD103, GITR, CTLA‐4 in mice, as well as in human [12, 15, 20].…”
Section: Cd8+ Foxp3+ T Cellsmentioning
confidence: 99%
“…Both classes have the same CD4 + CD25 + CD127 low phenotype and express the transcription factor forkhead box P3 (FOXP3). Studies using preclinical models and clinical trials found that Tregs prevent autoimmune disease and graft-versus-host disease (GVHD) 2 . The shortage of tTregs impedes the development of Treg therapy 3 .…”
Section: Introductionmentioning
confidence: 99%